Safety and efficacy of atezolizumab in patients with autoimmune disease: Subgroup analysis of the SAUL study in locally advanced/metastatic urinary tract carcinoma. (October 2020) - Loriot, Yohann; Sternberg, Cora N.; Castellano, Daniel; Oosting, Sjoukje F.; Dumez, Herlinde; Huddart, Robert; Vianna, Karina; Alonso Gordoa, Teresa; Skoneczna, Iwona; Fay, Andre P.; Nolè, Franco; Massari, Francesco; et al.
Abstract: Aim: Patients with pre-existing autoimmune disease (AID) are typically excluded from clinical trials of immune checkpoint inhibitors, and there are limited data on outcomes in this population. The single-arm international SAUL study of atezolizumab enrolled a broader 'real-world' patient population. We present outcomes in patients with a history of AID. Methods: Patients with locally advanced/metastatic urinary tract carcinoma received atezolizumab 1200 mg every 3 weeks until loss of clinical benefit or unacceptable toxicity. The primary end-point was safety. Overall survival (OS) was a secondary end-point. Subgroup analyses of AID patients were prespecified. Results: Thirty-five of 997 treated patients had AID at baseline, most commonly psoriasis ( n =  15). Compared with non-AID patients, AID patients experienced numerically more adverse events (AEs) of special interest (46% versus 30%; grade ≥3 14% versus 6%) and treatment-related grade 3/4 AEs (26% versus 12%), but without relevant increases in treatment-related deaths (0% versus 1%) or AEs necessitating treatment discontinuation (9% versus 6%). Pre-existing AID worsened in four patients (11%; two flares in two patients); three of the six flares resolved, one was resolving, and two were unresolved. Efficacy was similar in AID and non-AID patients (median OS, 8.2 versus 8.8 months, respectively; median progression-free survival, 4.4 versus 2.2 months; disease control rate, 51% versus 39%). Conclusions: In 35 atezolizumab-treated patients with pre-existing AID, incidences of special- interest and treatment-related AEs appeared acceptable. AEs were manageable, rarely requiring atezolizumab discontinuation. Treating these patients requires caution, but pre-existing AID does not preclude atezolizumab therapy. Trial registration: NCT02928406. Highlights: Data are limited on patients with autoimmune disease (AID) receiving immunotherapy. SAUL evaluated atezolizumab in a broad population with urinary tract carcinoma. Subgroup analyses of 35 atezolizumab-treated patients with AID were prespecified. Treatment-related adverse events were manageable. Treating AID patients with atezolizumab requires caution, but AID is not a barrier.